2018
DOI: 10.5430/jnep.v9n2p20
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infrared lamp therapy on episiotomy wound restorative besides pain relief among post-partum women

Abstract: Pregnancy and labor are exceptional occasions in women’s lives. Post-delivery is a very decisive period for compassionate woman who had under gone episiotomy which is a throbbing and disquiet procedure during this time. So, the aim of this study was to appraise the effect of infrared lamp therapy on episiotomy wound restorative besides pain relief among post-partum women. Post-partum women who apply infrared lamp therapy on episiotomy display faster wound restorative besides pain relief than those who do not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The author further added that dry heat is superior due to the fact that it continues for a longer duration than a moist one, keeps the wound dry, and improves healing. The present finding is also consistent with the study done by El-Lassy and Madian [ 24 ]; who found that the pain mean score was statistically significantly lower after the application of infrared lamp therapy among the study group than the control one. In addition, Gomathi et al [ 25 ] reported that the infrared light application was effective in relieving pain levels among postnatal mothers.…”
Section: Discussionsupporting
confidence: 93%
“…The author further added that dry heat is superior due to the fact that it continues for a longer duration than a moist one, keeps the wound dry, and improves healing. The present finding is also consistent with the study done by El-Lassy and Madian [ 24 ]; who found that the pain mean score was statistically significantly lower after the application of infrared lamp therapy among the study group than the control one. In addition, Gomathi et al [ 25 ] reported that the infrared light application was effective in relieving pain levels among postnatal mothers.…”
Section: Discussionsupporting
confidence: 93%
“…One of the main concerns of health workers during the puerperium is to provide comfort to the mother, help relieve pain and prevent infection. Therefore, improving episiotomy wound healing is one of the main concerns after normal delivery [1]. With regard to nonpharmacological methods, common practice is the use of ice packs, and the application of heat.…”
Section: Infrared Lightmentioning
confidence: 99%
“…The use of infrared therapy has proven to be able to improve the condition of the wound. Infrared therapy is an appropriate surrogate intervention for those with episiotomy injuries and has biologic results in cutaneous vasodilation due to the release of chemical vasodilators, histamine, and parallel materials, along with potential direct consequences on blood vessels [1].…”
Section: Infrared Lightmentioning
confidence: 99%
See 2 more Smart Citations